LITERACY OF OUR YOUNGSTERS: RESULTS AND RESTRAINTS FROM PISA - Hayat, Bahrul (UPI Press, 2010)
This article focused on results of assessment of PISA on level of literacy of youngsters in a number of countries including Indonesia. Key findings comprised reading literacy, mathematics literacy, and science literacy of Indonesian youngsters and those of other countries are described. Several factors assumed to have impacts on the results of assessment covered impacts of gender, engagement on learning, family background, and school characteristics. There are several constraints faced by Indonesia that make the assessment result unsatisfying, namely, input and process of education. Constraints of education input cover 1) insufficient availability of educators and educational staff; 2) unavailable learning facilities or inefficient use of the facilities; and 3) inadequate education costs. Constraints of education process comprise 1) too much structured and heavily loaded content, and 2) teacher oriented instructional method. The constraints of education process cause instructional process ineffective. There are seven solutions that need to be organized to cope with the constraints. They are 1) the development of better curriculum, learning method, and assessment system, 2) the capacity of educators’ profession, 3) the improvement of facilities and learning materials, 4) a life skill education, 5) the development of a superior school on basic education, 6) the improvement of quality and relevance of education, 7) the use of ICT for schooling and learning system.